Varicocele in Male Infertility: Current Status of Surgery Techniques - Oktay Üçer; Bilal Gümüş (European Medical Journal, 2015)
Varicocele is the most common cause of male infertility and is generally correctable, or at least improvable, through various surgical techniques. Although several different techniques for varicocele repair have been described in the literature, microsurgical subinguinal varicocelectomy is recognised as the gold-standard approach for varicocelectomy due to high success rates with minimal complications. This article reviews the current status of the effects of varicocelectomy techniques on male infertility and the recurrence and complication rates associated with these techniques.